(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chewing tobacco and using tobacco-based products can lead to poor health outcomes. Understanding the factors associated with tobacco use and smoking is important for interventions.In this study, the knowledge of slum women about their environmental health was assessed by applying an Ex-post facto research design. The study aimed to develop a health education programme for female respondents, implement it, and evaluate its impact. Multistage random sampling design was used, with purposive selection of the state of Uttar Pradesh and the city of Varanasi. Out of 12 wards in Varanasi, three - Shivpur, Dashashvamedha and Nagwa were randomly selected, and one slum from each ward was also randomly selected. Afterwards, 90, 150, and 84 families were respectively selected from Indarpur, Naria and Jangambadi, through proper allocation based on the population of these slums. Thus, the sample size for the present study consisted of 324 women from slums.